Broad-band and broad-angle linear and circular polarization converting metasurface. Issue 8 (24th May 2022) - Kamal, Babar; Chen, Jingdong; Yin, Yingzeng; Ren, Jian; Ullah, Sadiq; Khan, Bilawal
Abstract : This paper presents a broad-band and broad-angle anisotropic reflective polarization converting metasurface (PCMS) for C- and X-band applications, which is composed of square split ring resonators. Such PCMS can be used in a wide range of applications such as satellite antennas, navigation systems, and biomedical devices, to name but a few. The performance of the presented PCMS is analyzed theoretically, numerically, and experimentally. The results at normal and oblique incidences demonstrate that the PCMS achieves broad-band linear polarization (LP) transformation within an operating bandwidth of 5.3 GHz (5.3–10.6 GHz), covering the C-band and a portion of the X-band. The broad-band performance of the PCMS sustains from 0 ∘ to 60 ∘ . Moreover, the PCMS achieves polarization conversion for circularly polarized (CP) waves in the same bands. The polarization conversion ratio is more than 90 % for both LP and CP incident waves.